LingoLand: The Academic Quest - Azamri, Nurul Munirah; Ab. Mutalib, Halimatun Saadiah; Ibrahim, Nooraileen (2025)
This study introduces LingoLand: The Academic Quest, a board game that is designed to assist in the development of Academic English skills among undergraduate learners at a public university in Perak. The game incorporates key language domains such as grammar, vocabulary, speaking, writing, and cultural awareness within a gamified framework that initiates collaborative learning and active participation among the students. Players engage in meaningful language tasks that enhance fluency, accuracy, and critical thinking by passing through thematic zones and skill-targeted challenges. The flexible design accommodates physical play, making it adaptable to be played by students in class. Preliminary classroom implementation suggests that LingoLand effectively motivates learners and fosters peer interaction, providing a novel and scalable approach to academic language acquisition.